Multi-ceramic coupling diamond-structured photonic crystals based on rapid prototyping technology and its controllable microwave electromagnetic forbidden gap properties. Issue 3 (April 2015) - Liang, Qingxuan; Li, Dichen; Yang, Gai; Chen, Tianning
Abstract: The multi-ceramic coupling diamond-structured photonic crystals containing alumina and yttria simultaneously were successfully fabricated by rapid prototyping based on stereolithography and multi-step gel-casting process. The lattice constant of the photonic crystal structures was chosen as 7 mm and the measured forbidden gap range lies between 27.2 GHz and 34.9 GHz. The gradually varied solid loading in volume of Al2 O3 powder and its controllable electromagnetic forbidden gap properties were investigated in such photonic crystals. It was found that, as the solid loading of Al2 O3 powder increased, the electromagnetic forbidden gap width gradually increased and the center frequency shifted to a lower frequency when electromagnetic waves transmitted along the coupling direction of photonic crystals. When the solid loading reached 60 vol%, electromagnetic forbidden gap of the photonic crystals was observed from 27.2 GHz to 34 GHz, and the forbidden gap width was 6.8 GHz which was 126.4% of that of the yttria photonic crystal (the forbidden gap from 30.9 GHz to 35.9 GHz) and 115.3% of that of the alumina photonic crystal (60 vol%, the forbidden gap from 26.4 GHz to 32.3 GHz). These results indicate that a diamond-structured photonic crystal with multi-ceramic coupling could effectively expand the electromagnetic forbidden gap width and may be beneficial for applications of photonic crystals in device. Moreover, this work offers a rapid prototyping technology to three-dimensional photonic crystals with considerable flexibility of materials choice.